New species in the family Ctenidae Keyserling, 1877 from high altitude habitats in Myanmar, with the first case of penetration of the female’s cuticle by a male in the RTA-clade (Arachnida: Araneae: Ctenidae) - Jäger, Peter; Minn, Myin Zu (Zootaxa, 2015)
Specimens of the spider genera Ctenus Walckenaer, 1805 and Anahita Karsch, 1879 from Myanmar were investigated. Three species are described as new to science: Anahita popa spec. nov. (female; Mt Popa), Ctenus natmataung spec. nov. (male, female; Mt Victoria) and C. pingu spec. nov. (male, female; Mt Victoria). The female of C. cladarus Jäger, 2012 is described for the first time. Males of C. natmataung spec. nov. possess an easily breakable tip of their RTA. Two cases are reported where this part was clinging to the epigyne and a pointed appendix had penetrated the female’s cuticle. This is the first such case reported within the RTA-clade. All three Ctenus spp. have very similar copulatory organs and are interpreted as a product of relatively recent speciation events. According to their elevational zonation, the driving factor for this speciation could be different climatic conditions at different elevations.